Üniversite öğrencilerinde bağlanma stilleri ve kendine saygı ile ilişki doyumu arasındaki ilişkide aldatılma algısının aracı rolü - Çelimli, Çağla (My University, 2022)
Bu araştırmada, üniversite öğrencilerinin bağlanma sitilleri (güvenli ve kayıtsız), kendine saygı (olumlu olumsuz) ile ilişki doyumları arasındaki ilişkide aldatılma algısının aracılık rolü incelenmiştir. Araştırmaya 18-30 yaş aralığında romantik ilişkisi olan 633 üniversite öğrencisi katılmıştır. Araştırmada veri toplama aracı olarak, Romantik İlişki Doyumu Ölçeği (RİDÖ), İlişki Ölçekleri Anketi (İÖA), Kendine Saygı Ölçeği (KSÖ), Aldatılma Algısı Ölçeği (AAÖ) ve Kişisel Bilgi Formu kullanılmıştır. AAÖ, bu araştırma kapsamında araştırmacı tarafından geliştirilmiştir. Ölçeği geliştirme süreci 575 kişi ile yürütülmüştür. Yapılan analizler sonucunda 28 maddelik ölçeğin 19 madde “belirgin boyut” ve 9 madde de “belirsiz boyut” olmak üzere iki boyuttan oluştuğu ortaya çıkmıştır. Araştırmanın örneklemi olasılık temelli örneklem yöntemine dayalı “uygun örnekleme” ve “ölçüt örnekleme” türlerine göre belirlenmiştir. Verilerin analizinde SPSS 21 paket MPLUS 6.12 paket programından yararlanılmıştır. SPSS paket versite öğrencilerinin ilişki doyum düzeylerinin demografik özelliklerine göre anlamlı farklılık gösterip göstermedikleri Bağımsız Gruplar t Testi ve F Testi (One-Way ANOVA) kullanılarak hesaplanmıştır. Test edilen modelin sonucuna göre, güvenli bağlanma ve ilişki doyumu arasındaki ilişkide aldatılma algısının kısmi aracı rolü olduğu, kayıtsız bağlanma ve ilişki doyumu arasındaki ilişkide aldatılma algısının kısmi aracılık rolü olduğu, olumlu kendine saygı ve ilişki doyumu arasındaki ilişkide aldatılma algsının kısmi aracılık rolü olduğu ve olumsuz kendine saygı ve ilişki doyumu arasındaki ilişkide aldatılma algısının kısmi aracılık rolü olduğu Yapısal Eşitlik Modeli kullanılarak bulunmuştur. Son olarak da, araştırmadan elde edilen sonuçlar literatür ve kuramlar bağlamında tartışılmış, gelecekte yapılacak araşırmalara ve Psikolojik Danışmanlık ve Rehberlik alanına yönelik öneriler sunulmuştur.

In this study, the mediating role of perception of infidelity in the relationship between university students' attachment styles (secure and dismissive), self-esteem (positive and negative) and relationship satisfaction was investigated. 633 university students between the ages of 18-30 who had a romantic relationship, participated in the study. In the study, Relationship Satisfaction Inventory (RSI) Relationship Scales Questionnaire (RSQ), SelfRespect Scale (SRS), Perception of Infidelity Scale (PIS) and Personal Information Form were used as data collection tools. AAO was developed by the researcher within the scope of this research. The scale development process was carried out with 575 people. As a result of the analyzes made, it was revealed that the 28-item scale consisted of two dimensions, 19 of which were the clear dimension and 9 items were the uncertain dimension. The sample of the study was determined according to the types of “appropriate sampling” and “criterion sampling” based on the probability-based sampling method. SPSS 21 package program and MPLUS 6.12 package program were used in the analysis of the data. In the analysis of the data, in order to answer the research questions determined within the framework of the research objectives, whether the relationship satisfaction levels of university students differ significantly with the SPSS package program according to their demographic characteristics were calculated using the Independent Groups t-Test and the F-Test (One-Way ANOVA). According to the results of the structural model, the perception of being deceived has a partial mediating role in the relationship between secure attachment and relationship satisfaction. The perception of being deceived has a partial mediating role in the relationship between dismissive attachment and relationship satisfaction, The perception of infideltiy has a partial mediating role in the relationship between positive self-respect and relationship satisfaction and the perception of being deceived has a partial mediating role in the relationship between negative self-respect and relationship satisfaction. Finally, the results obtained from the research were discussed in the context of literature and theories, and suggestions for future research and the field of Psychological Counseling and Guidance were presented.
The intermediate role of the perception of being deceived in the relationship between attachment styles and self-respect and relationship satisfaction in university students
Keywords: Aldatılma Algısı; Dismissive Attachment; Doyum Secure Attachment; Education; Eğitim; Güvenli Bağlanma; İlişki; Kayıtsız Bağlanma; Perception of Infidelity; Psikolojik danışmanlık ve rehberlik; Psychological counseling and guidance; Relationship Satisfaction